A Genome-Wide Screen for Dendritically Localized RNAs Identifies Genes Required for Dendrite Morphogenesis. Issue 8 (1st August 2016) - Misra, Mala; Edmund, Hendia; Ennis, Darragh; Schlueter, Marissa A; Marot, Jessica E; Tambasco, Janet; Barlow, Ida; Sigurbjornsdottir, Sara; Mathew, Renjith; Vallés, Ana Maria; Wojciech, Waldemar; Roth, Siegfried; et al.
Abstract: Localizing messenger RNAs at specific subcellular sites is a conserved mechanism for targeting the synthesis of cytoplasmic proteins to distinct subcellular domains, thereby generating the asymmetric protein distributions necessary for cellular and developmental polarity. However, the full range of transcripts that are asymmetrically distributed in specialized cell types, and the significance of their localization, especially in the nervous system, are not known. We used the EP-MS2 method, which combines EP transposon insertion with the MS2 /MCP in vivo fluorescent labeling system, to screen for novel localized transcripts in polarized cells, focusing on the highly branched Drosophila class IV dendritic arborization neurons. Of a total of 541 lines screened, we identified 55 EP-MS2 insertions producing transcripts that were enriched in neuronal processes, particularly in dendrites. The 47 genes identified by these insertions encode molecularly diverse proteins, and are enriched for genes that function in neuronal development and physiology. RNAi-mediated knockdown confirmed roles for many of the candidate genes in dendrite morphogenesis. We propose that the transport of mRNAs encoded by these genes into the dendrites allows their expression to be regulated on a local scale during the dynamic developmental processes of dendrite outgrowth, branching, and/or remodeling.